Peligro sa rabies atong likayan a communication plan for raising awareness and practices on rabies prevention and control in Davao City - Dela Cerna, Kairos Christine P.; Glova, Nelfa M. (2019)
This study aimed to create a communication plan that would raise the awareness and practices on Rabies Prevention and Control Strategies in Davao City. The researcher used the Health Belief Model (HBM) to determine the health-related behavioral change of the respondents in response to the six risks perceptions. This study explored the (1) socio-demographic characteristics of the respondents; (2) determine the prior information scanning related to dog rabies; (3) identify the prior knowledge of the respondents on dog rabies; (4) determine the practices of the respondents towards responsible dog ownership; (5) and find out the relationship of the six risk perceptions, information scanning, knowledge, and the preventive behaviors of the respondents. Using the mixed method design, the researcher conducted the study on the three barangays in Davao City that had the highest rabies cases in 2018. There were two hundred (200) respondents surveyed, three opinion leaders interviewed, and two sets of Focus Group Discussions (FGDs) conducted to gather data that were important in the communication plan. Overall, the results showed that respondents had low prior exposure on dog rabies, low knowledge about dog rabies prevention and control, low practices of responsible pet ownership, and low information scanning about dog rabies and its effects. Moreover, the six (6) risk perceptions correlated with each other while the age, educational attainment, gender, and occupation of the respondents had significant relationships with the risk perceptions. These results deemed important implications for the creation of the communication plan and provide data for future health communication campaigns.
Thesis (BA Communication Arts) -- University of the Philippines Mindanao, 2019